Gaming alone or together? L2 beginner-level gaming practices - Marta Gonzalez-Lloret; María Diez Ortega (Universidade Federal de Santa Catarina, 2020)
Games are seen as beneficial for language learning because they facilitate rich, authentic communication, and promote collaborative practices which are effective for language learning. However, most of the studies to date investigating games for L2 learning have focused on intermediate or advanced learners, and we know very little of how games can be best utilized with beginner-level learners. This study investigates beginner-level learners of Spanish engaged in a task-based educational game in which they interacted through an avatar with game characters in a study abroad setting. Although the game is designed to be played individually, we hypothesized that playing collaboratively would bring more language negotiation, which in turn promotes language acquisition (SWAIN, 2000). Four intact first semester classes in a US university participated in the research. Two classes acted as control group and engaged in technology activities that were not the game and two classes played the game either individually or in dyads. Students' grammar, vocabulary, reading, and writing were compared after the treatment. In addition, pre- and post-treatment motivation surveys were conducted to find out students' perspectives on the game playing and whether their opinions had changed after the experience. Although students gaming in dyads outperformed the other groups in all measures, the differences were not statistically significant. However, there were clear differences in the learners' perspective towards playing in dyads versus playing individually. In addition, the qualitative analysis of the data revealed multiple instances of language related episodes which have been demonstrated beneficial for language learning.